2018
DOI: 10.1002/jmri.26028
|View full text |Cite
|
Sign up to set email alerts
|

Variable impact of CSF flow suppression on quantitative 3.0T intracranial vessel wall measurements

Abstract: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;48:1120-1128.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 17 publications
(33 reference statements)
3
25
0
Order By: Relevance
“…As the changes in wall thickness with age are submillimeter, the changes are often subtle on qualitative inspection. Regardless, at the spatial resolution of recently proposed 3T VWI sequence parameters, quantitative evaluation does demonstrate on average a small increase in wall thickness with age. Scatterplots suggested that the detected vessel wall changes with age were predominantly occurring in subjects greater than 50 years old.…”
Section: Discussionmentioning
confidence: 81%
“…As the changes in wall thickness with age are submillimeter, the changes are often subtle on qualitative inspection. Regardless, at the spatial resolution of recently proposed 3T VWI sequence parameters, quantitative evaluation does demonstrate on average a small increase in wall thickness with age. Scatterplots suggested that the detected vessel wall changes with age were predominantly occurring in subjects greater than 50 years old.…”
Section: Discussionmentioning
confidence: 81%
“…All participants received a non‐contrast 3T brain MRI and an MRA with standard anatomical imaging, including VW‐MRI [3D turbo‐spin‐echo (TSE) factor = 56; TR/TE = 1500/33 ms; refocusing angle sweep = 40°–120°; in‐plane spatial resolution = 0·5 × 0·5 mm], 20,21 T 2 ‐weighted (3D TSE factor = 15; TR/TE = 4000/83 ms; refocusing angle sweep = 40°–120°; spatial resolution = 0·5 × 0·5 × 2·4 mm), fluid‐attenuated inversion recovery (FLAIR; turbo inversion recovery; spatial resolution = 0·6 × 0·6 × 3·0 mm; TR/TI/TE = 11,000/2800/120 ms), diffusion weighted imaging (DWI; single‐shot echo planar imaging; spatial resolution = 1·8 × 1·8 × 4 mm; b‐values of 0 and 1000 s/mm 2 ) and intracranial time‐of‐flight MR angiography (3D gradient echo; spatial resolution = 0·4 × 0·4 × 1·4 mm 3 ; TR/TE = 23/3·5 ms). To evaluate whether vessel wall thickening may be related to flow velocities, we performed phase contrast angiography (PCA) of major anterior and posterior vessels using a previously reported protocol 22 with in‐plane spatial resolution = 0·5 x 0·5 mm 2 , TR/TE = 20/7 ms, v enc = 40 cm/s.…”
Section: Methodsmentioning
confidence: 99%
“…Images were then reformatted in a plane orthogonal to the vessel course (Fig 1) at the following locations: supraclinoid ICA (left and right separately) and mid‐basilar artery between the superior cerebellar artery and anterior inferior cerebellar artery. These segments were the focus of the study, due to the higher established reproducibility of vessel wall thickness measurements in these vessels in non‐atherosclerotic vascular disease patients at the afforded spatial resolution of 3T VW‐MRI, compared with more distal measurements in the middle cerebral arteries 20,21 . Luminal diameters and outer vessel wall diameters were measured perpendicular to the vessel course using the OsiriX multiplanar reformatting tool.…”
Section: Methodsmentioning
confidence: 99%
“…31 In many cases, these VWI studies need confirmation with additional work to show reproducibility and validity in various patient populations if these findings are to be used to heavily influence clinical care. Readers should take into account spatial resolution and type of flow-suppression technique, as these technical factors can impact the appearance of vessel wall 12 and vessel wall enhance- ment. Additionally, the methods of image interpretation and criteria used to establish the final diagnosis need careful consideration.…”
Section: High-resolution Vessel Wall Imagingmentioning
confidence: 99%